Cardiovascular magnetic resonance stress and rest T1-mapping using regadenoson for detection of ischemic heart disease compared to healthy controls. (15th June 2021) - Burrage, Matthew K.; Shanmuganathan, Mayooran; Masi, Ambra; Hann, Evan; Zhang, Qiang; Popescu, Iulia A.; Soundarajan, Rajkumar; Leal Pelado, Joana; Chow, Kelvin; Neubauer, Stefan; Piechnik, Stefan K.; Ferreira, Vanessa M.
Abstract: Background: Adenosine stress T1-mapping on cardiovascular magnetic resonance (CMR) can differentiate between normal, ischemic, infarcted, and remote myocardial tissue classes without the need for contrast agents. Regadenoson, a selective coronary vasodilator, is often used in stress perfusion imaging when adenosine is contra-indicated, and has advantages in ease of administration, safety profile, and clinical workflow. We aimed to characterize the regadenoson stress T1-mapping response in healthy individuals, and to investigate its ability to differentiate between myocardial tissue classes in patients with coronary artery disease (CAD). Methods: Eleven healthy controls and 25 patients with CAD underwent regadenoson stress perfusion CMR, as well as rest and stress ShMOLLI T1-mapping. Native T1 values and stress T1 reactivity were derived for normal myocardium in healthy controls and for different myocardial tissue classes in patients with CAD. Results: Healthy controls had normal myocardial native T1 values at rest (931 ± 22 ms) with significant global regadenoson stress T1 reactivity (δT1 = 8.2 ± 0.8% relative to baseline; p  < 0.0001). Infarcted myocardium had significantly higher resting T1 (1215 ± 115 ms) than ischemic, remote, and normal myocardium (all p < 0.0001) with an abolished stress T1 response (δT1 = −0.8% [IQR: −1.9–0.5]). Ischemic myocardium had elevated resting T1 compared to normal (964 ± 57 ms; p  < 0.01) with an abolished stress T1 response (δT1 = 0.5 ± 1.6%). Remote myocardium in patients had comparable resting T1 to normal (949 ms [IQR: 915–973]; p  = 0.06) with blunted stress reactivity (δT1 = 4.3% [IQR: 3.1–6.3]; p  < 0.0001). Conclusions: Healthy controls demonstrate significant stress T1 reactivity during regadenoson stress. Regadenoson stress and rest T1-mapping is a viable alternative to adenosine and exercise for the assessment of CAD and can distinguish between normal, ischemic, infarcted, and remote myocardium. Highlights: Regadenoson has advantages over adenosine in terms of administration, safety profile, and clinical workflow. There are distinct tissue characteristics for normal, ischemic, infarcted, and remote myocardium. Healthy controls demonstrate significant stress T1 reactivity during vasodilator stress. Regadenoson stress T1-mapping can distinguish between different myocardial tissue classes. Regadenoson stress T1-mapping is a viable alternative to adenosine and exercise for the assessment of coronary artery disease.